2017
DOI: 10.1083/jcb.201606078
|View full text |Cite
|
Sign up to set email alerts
|

The Vps13p–Cdc31p complex is directly required for TGN late endosome transport and TGN homotypic fusion

Abstract: VPS13 proteins are widely conserved in eukaryotes and associated with human neurodegenerative and neurodevelopmental diseases. De et al. describe the lipid specificity and structure of yeast Vps13p, providing insight into its role in both TGN late endosome transport and TGN homotypic fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
116
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(128 citation statements)
references
References 59 publications
8
116
0
4
Order By: Relevance
“…This is unexpected because both N‐terminal and C‐terminal regions are evolutionarily conserved and similar to the corresponding regions in VPS13A. An in vitro liposome experiment showed that yeast Vps13 can directly bind to membranes, especially those containing phosphatidic acid and phosphatidylinositol phosphates . In particular, the N‐terminal region of Vps13 showed a high affinity to phosphatidic acid and a weak affinity to PtdIns4,5P 2 and PtdIns4P, whereas the C‐terminal region showed an affinity to PtdIns4,5P 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This is unexpected because both N‐terminal and C‐terminal regions are evolutionarily conserved and similar to the corresponding regions in VPS13A. An in vitro liposome experiment showed that yeast Vps13 can directly bind to membranes, especially those containing phosphatidic acid and phosphatidylinositol phosphates . In particular, the N‐terminal region of Vps13 showed a high affinity to phosphatidic acid and a weak affinity to PtdIns4,5P 2 and PtdIns4P, whereas the C‐terminal region showed an affinity to PtdIns4,5P 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that Vps13 is required for normal sorting of Neo1 flippase on endosomes . The observed defects in Golgi‐to‐vacuole transport and in endocytosis might occur as the result of misregulation of common components of both pathways or as a direct consequence of Vps13 deficiency, as it has been reported recently that Vps13 is directly required for Golgi‐to‐endosome transport and trans‐Golgi homotypic fusion in vitro …”
Section: Yeast As a Model To Study Vps13 Proteinsmentioning
confidence: 94%
“…Vps13 is folded into a compact rod shape (20 × 4 nm) with a flexible portion in the middle, a characteristic loop structure with internal diameter of ∼6 nm at one end and a hook‐like region on the opposite end. Such ending structures can be facing the same or opposite directions suggesting the possibility of rotation (Figure B) . The position of the N‐ and C‐terminal regions in this structure is still unknown.…”
Section: Yeast As a Model To Study Vps13 Proteinsmentioning
confidence: 98%
See 2 more Smart Citations